Passion Fruit Cultivation: An Approach to Internal Leaf Anatomy - Manzani Lisboa, Lucas Aparecido [UNESP]; Cavichioli, José Carlos; Ferreira, Thiago de Souza; da Silva, Aldeir; de Figueiredo, Paulo Alexandre Monteiro [UNESP] (MDPI, 2024)
Some species of the genus Passiflora have leaf morphological adaptations that grow to influence the development of the plant in producing areas. Hence, the objective of this work is to quantify and characterize the leaf anatomy of passion fruit species distributed in the South American region, which can become an important strategy in the selection of species more adapted to the environment where they will be grown. This work evaluates the abaxial and adaxial cuticle thickness (ABCT and ADCT), abaxial and adaxial epidermis thickness (ABET and ADET), xylem diameter (XD), phloem diameter (PD), and thickness of the palisade parenchyma (TPP), of the species Passiflora quadrangularis L., Passiflora foetida L., Passiflora edulis Sims, Passiflora gibertii N.E Brown, Passiflora coccinea Aubl, Passiflora alata Curtis, Passiflora tenuifila Killip, Passiflora caerulea L., and Passiflora cincinnata Mast. Passion fruit species present differences in leaf anatomy, which may influence the plant’s development. The species Passiflora quadrangularis L. showed a greater thickness of cuticles, epidermis, conducting vessels, and palisade parenchyma. The species Passiflora edulis has higher density and stomatal functionality. All Passiflora species formed druses on their leaves.
Keywords: druses; Passifloraspp; phloem; plant morphology; xylem